Penerapan Instrumen Three-Tier Test untuk Mengidentifikasi Miskonsepsi Siswa SMA pada Materi Keseimbangan Benda Tagar - Budi Astuti; Aufa Maulida Fitrianingrum; Sarwi Sarwi (Phenomenon : Jurnal Pendidikan MIPA, 2017)
The purpose of this research was to identify and analyze the students’misconceptions ofrigid body equilibrium concept. This research was included inertia moment, torque, andcentre of gravity concept. This reseacrh used qualitative method. There were 35 students assample chosen by purposive sampling technique. The research data was obtained bydiagnostic test used three-tier test. Based on the qualitative analysis result to the students’answers could be conclude that there were misconceptions. The high misconceptions werehappenned in moment inertia concept and cognitive domain “remember”.